Regulacje prawne odpowiedzialności konstytucyjnej Prezydenta Federalnego Niemiec - Grabowska, Sabina (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
The text is an analysis of the German legal regulations concerning the constitutional responsibility of the President. Federal President of Germany for committing aconstitutional delict is responsible before the Federal Constitutional Court. The proposal in this regard may submit a group of parliamentarians and parliament puts indictment. If the Federal Constitutional Court decides the merits of allegations made in the indictment, the president shall be deposited with the office.
Keywords: Niemcy; Prezydent Federalny Niemiec; odpowiedzialność konstytucyjna; regulacje prawne